The Impact of Fraud Risks and Uncertainties on Business Activities under Sanctions Restrictions - V. V. Zemskov (Учёт. Анализ. Аудит, 2024)
This study examines and addresses the most important and critical problems associated with fraud risks and uncertainties in accounting (financial) and tax reporting. Attackers, committing deceptive and fraudulent actions, overestimate assets or write off stolen funds as expenses, as a result of which potential investors, suppliers, and customers may make incorrect financial decisions regarding the alleged counterparty. The author of the article analyzes the uncertainties existing in tax legal relations, and how they divert the resources of business entities (financial, human, technological) to resolve these problems through litigation. The purpose of the study is to analyze and assess both the risks of fraudulent misstatements with estimated liabilities and fair values in financial statements, as well as uncertainties affecting business activities and operations in the conditions of limited financial resources. The risks of fraud and uncertainty act as the key factors in predictive crimes and offences. The article presents the author’s interpretation of the concept of “uncertainty” as the inability of a management entity to make the right financial decisions due to ignorance of relevant regulatory legal documents on various issues of tax relations or incomplete information necessary for effective activity. The study used such general scientific methods as comparative and logical analyses, statistical analysis, and content analysis. The author of the study concluded that when identifying existing uncertainties in tax legal relations, when some of them are not legally regulated, the principle of presumption of innocence of an economic entity should be applied, which, under the conditions of sanctions restrictions, is the only correct decision that directly affects the financial well-being of the latter, and, consequently, the level of the country’s defense capability. The results of the study can be used in practice by employees of financial, accounting services, as well as the employees of regulatory and supervisory authorities in assessing tax risks.